Ramayana In Java A Study Of Visual Art Style Transformation - Kusen (Balai Arkeologi Yogyakarta, 1990)
A transformation of a story into a visual form is not a simple thing because there are many factors involved in this process. The major thing faced by an artist is how to get a model for the figure being made. From a general point of view there are two basic ways of transforming a story into a visual form. The first one is that the artist creates a figure based on his or her own imagination and interpretation of the character of a hero described in the story. The second one is that the artist just copies a previous form precisely or with modifications.